2004
DOI: 10.1080/00016480310017045
|View full text |Cite
|
Sign up to set email alerts
|

Otologic consequences of blast exposure: a finnish case study of a shopping mall bomb explosion

Abstract: People often think that tinnitus and hearing impairment are naturally occurring phenomena after blast exposure, and if their symptoms resolve they do not seek medical advice. However, some of them may have substantial hearing impairment, particularly at high frequencies. Otologic consultation, or at least an audiometric screening test to exclude hearing impairment, should be performed regardless of symptoms, on the basis of exposure data only. Some symptoms, such as tinnitus and hearing loss, may be permanent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 8 publications
5
51
0
9
Order By: Relevance
“…This damage is primarily mechanical, as the force of the blast wave tears the sensory cells and displaces the basilar membrane. Otologic injury is usually present at the time of the blast, producing temporary or permanent hearing loss and/or tinnitus [20]. Typically, sustained high-intensity noise causes more sensorineural damage than a single, very high-intensity blast [18].…”
Section: Inner Ear Injury: Cochlear Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…This damage is primarily mechanical, as the force of the blast wave tears the sensory cells and displaces the basilar membrane. Otologic injury is usually present at the time of the blast, producing temporary or permanent hearing loss and/or tinnitus [20]. Typically, sustained high-intensity noise causes more sensorineural damage than a single, very high-intensity blast [18].…”
Section: Inner Ear Injury: Cochlear Injurymentioning
confidence: 99%
“…Blast exposure most commonly results in pure SNHL, with a 35 to 100 percent incidence rate in blastinjured patients [2,19,20,[22][23][24]. Of blast-injured soldiers treated at Walter Reed Army Medical Center in 2005, 64 percent had ongoing hearing loss [5].…”
Section: Inner Ear Injury: Cochlear Injurymentioning
confidence: 99%
“…They attributed this higher rate to the fact that their data were extracted from an audiology clinic database. Mrena et al assessed the otologic and audiologic outcomes of 29 patients treated for ear injury after a Finland shopping mall explosion [27]. They found that 66 percent reported tinnitus as their initial symptom, and 55 percent reported hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many forms of acoustic exposures, blast, a high-energy impulse noise, has received significant attention lately due to the large number of injured soldiers who were involved in recent war operations in Iraq and Afghanistan. Blast can induce a wide range of pathologies in the body, including auditory pathology such as tinnitus and hearing loss, as well as traumatic brain injury (TBI; Breeze et al, 2011;Dougherty et al, 2011;Fausti et al, 2009;Lew et al, 2009;Mrena et al, 2004aMrena et al, ,2002Okie, 2005). Ear injuries constitute the single most frequent injury type sustained in the Iraq War (Gondusky and Reiter, 2005).…”
Section: Introductionmentioning
confidence: 99%